Asymptotic Estimates for r-Whitney Numbers of the Second Kind - Cristina B. Corcino; Roberto B. Corcino; Nestor Acala (Journal of Applied Mathematics)
The r-Whitney numbers of the second kind are a generalization of all the Stirling-type numbers of the second kind which are in line with the unified generalization of Hsu and Shuie. In this paper, asymptotic formulas for r-Whitney numbers of the second kind with integer and real parameters are obtained and the range of validity of each formula is established.